Dysregulation of serum miR-1204 and its potential as a biomarker for the diagnosis and prognosis of breast cancer - Han,Suli (2020)
SUMMARY OBJECTIVE A previous study has reported that miR-1204 exerted oncogenic effects in breast cancer (BC). The purpose of our paper was to evaluate the expressions of tissue and serum miR-1204 in patients with BC and further investigate its biomarker potential. METHODS The expressions of tissue and serum miR-1204 were investigated by qRT-PCR in 144 BC patients and 38 healthy controls. Chi-square tests were conducted to examine the associations between miR-1204 expressions and clinicopathological factors. Then, the associations of miR-1204s level with the survival of BC patients were determined by performing the Kaplan-Meier and multivariate analysis. The receiver operating characteristics (ROC) and area under the OC curve (AUC) were obtained to validate the diagnostic values of miR-1204. RESULTS We found that the expressions of miR-1204 were increased in both tissue and serum samples from BC patients. Multivariate assays identified tissue and serum miR-1204 overexpression as an independent poor prognostic factor. In addition, ROC curve assays indicated that tissue and serum miR-1204 are potential diagnostic markers of BC. CONCLUSIONS Detection of tissue and serum miR-1204 levels could have clinical potential as a novel prognostic/diagnostic biomarker for BC patients.